Emergency contraception among young people - S S Aganezov; A V Morotskaya; N V Aganezova (IP Berlin A.V., 2016)
Purpose of the study is to determine the frequency of the use of emergency contraception among young people and awareness of the emergency contraception in the youth environment. Material and methods. Analysis of data from anonymous questionnaires was received from 952 people from various educational institutions and by the young doctors of various specialties. The gender composition of participants was: girls - 802 (84.2%), boys -150 (15.8%) aged 15 to 24 years (mean age 20.7±1.6 years). Results. Pregnancy rates among young people is 9.9% and increases with age. Two-thirds of pregnancies were medically aborted. Every third woman (32.9%) has an experience in using emergency contraception. For the levonorgestrel, emergency contraception is used. Awareness about emergency contraception is low.